Childhood depression. A case of dysthymic - Brener Reyna, María Lorena (2002)
The following case is about a boy with distimic depression which dysfunctional family behavior avoiding a complete development of the person integral. The parents play an essential role for a complete development of the person integral attitude foe the live. Is very important that parents will be able to recognize there owns mistakes, before decided to have their own family and nailing when education owns children. Parents will be able raised kids own child conflicts. Other wise the history will be repeated.